The bZIP transcription factor SPA Heterodimerizing Protein represses glutenin synthesis in Triticum aestivum. (5th January 2019) - Boudet, Julie; Merlino, Marielle; Plessis, Anne; Gaudin, Jean‐Charles; Dardevet, Mireille; Perrochon, Sibille; Alvarez, David; Risacher, Thierry; Martre, Pierre; Ravel, Catherine
Summary: The quality of wheat grain is mainly determined by the quantity and composition of its grain storage proteins (GSPs). Grain storage proteins consist of low‐ and high‐molecular‐weight glutenins (LMW‐GS and HMW‐GS, respectively) and gliadins. The synthesis of these proteins is essentially regulated at the transcriptional level and by the availability of nitrogen and sulfur. The regulation network has been extensively studied in barley where BLZ1 and BLZ2, members of the basic leucine zipper (bZIP) family, activate the synthesis of hordeins. To date, in wheat, only the ortholog of BLZ2, Storage Protein Activator (SPA), has been identified as playing a major role in the regulation of GSP synthesis. Here, the ortholog of BLZ1, named SPA Heterodimerizing Protein (SHP), was identified and its involvement in the transcriptional regulation of the genes coding for GSPs was analyzed. In gel mobility shift assays, SHP binds cis ‐motifs known to bind to bZIP family transcription factors in HMW‐GS and LMW‐GS promoters. Moreover, we showed by transient expression assays in wheat endosperm that SHP acts as a repressor of the activity of these gene promoters. This result was confirmed in transgenic lines overexpressing SHP, which were grown with low and high nitrogen supply. The phenotype of SHP ‐overexpressing lines showed a lower quantity of both LMW‐GS and HMW‐GS, while the quantity of gliadin was unchanged, whatever the nitrogen availability. Thus, the gliadin/glutenin ratio was increased, which suggests that gliadin and glutenin genes may be differently regulated. Significance statement: The wheat paralog of the storage protein activator (SPA) and BLZ2 gene group, SPA heterodimerizing protein (SHP), was characterized. In vitro and in vivo DNA–protein interaction analysis and transgenic lines demonstrate that SHP represses glutenin synthesis.